ANALISIS KESULITAN MAHASISWA PENDIDIKAN GURU MI DALAM MENYUSUN PERENCANAAN PEMBELAJARAN KURIKULUM MERDEKA - I Mahmudah (Universitas Islam Darul 'Ulum Lamongan, 2023)
Palangka Raya is one of the provinces that has implemented an independent curriculum, therefore prospective Islamic elementary school teacher students must also be equipped with knowledge and skills in developing independent curriculum learning tools. So that when students do internships at schools or madrasas they are ready to adapt. The purpose of this study was to analyze MI teacher education students in developing independent curriculum learning plans. The research method used is qualitative research. Data collection techniques used are observation, interviews and documentation. The results of the study showed that students experienced the most difficulties in compiling independent curriculum learning tools when compiling learning objectives, namely 15 students. Then arrange the assessment experienced by 12 students. The next difficulty is determining the profile of Pancasila students experienced by 10 students. Furthermore, difficulties were experienced when making trigger questions and compiling enrichment and remedial which were experienced by 9 students. Determining the learning objectives and glossary experienced by 8 students, difficulties in determining the initial competence of 5 students, compiling student and teacher reflections experienced by 4 students, difficulties in learning activities experienced by 3 students and finally difficulty compiling a bibliography only experienced by 1 student person.